2016
DOI: 10.1111/fog.12185
|View full text |Cite
|
Sign up to set email alerts
|

Differing environmental drivers of settlement across the range of southern rock lobster (Jasus edwardsii) suggest resilience of the fishery to climate change

Abstract: Temporal and spatial trends in settlement of the southern rock lobster, Jasus edwardsii, were examined to identify the influence of environmental variables over different spatial scales. Settlement data were collected from 1994 to 2011 along the Southern Australian and New Zealand coasts. We identified common settlement trends at a regional scale (100–500 km): the magnitude of settlement at sites from South Australia (SA) and Victoria (VIC) were similar, but different to sites in Tasmania (TAS). In New Zealand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…These two distinct oceanic features created genetic patchiness along P. argus’ geographic range (Truelove et al., ). In the case of J. edwardsii , patterns of settlement abundance have also been attributed to oceanographic features that vary in strength and importance among regions (Hinojosa et al., ). An oceanographic model simulating larval transport of J. edwardsii suggested that there is a high degree of self‐recruitment in areas such as Cape Jaffa (Bruce et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These two distinct oceanic features created genetic patchiness along P. argus’ geographic range (Truelove et al., ). In the case of J. edwardsii , patterns of settlement abundance have also been attributed to oceanographic features that vary in strength and importance among regions (Hinojosa et al., ). An oceanographic model simulating larval transport of J. edwardsii suggested that there is a high degree of self‐recruitment in areas such as Cape Jaffa (Bruce et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that either the selective forces acting during early postsettlement of J. edwardsii differ across the geographic range of the species and from year to year, or that different loci are responding to the same selective pressure. Differences in selective pressures would be the most likely scenario given that climate‐ocean forces driving settlement in J. edwardsii are also variable across the species distribution (Hinojosa et al., ). As mentioned above, predation is the main source of mortality after settlement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations